Humanocracy : creating organizations as amazing as the people inside them - Hamel, Gary, (Harvard Business Review Press, 2020)
"Our organizations are failing us. They're sluggish, change-phobic, and emotionally arid. Human beings, by contrast, are adaptable, creative, and full of passion. This gap between individual and organizational capability is the unfortunate by-product of bureaucracy--the top-down, rule-choked management structure that undergirds virtually every organization on the planet. Invented in the nineteenth century with the goal of turning people into semi-programmable robots, bureaucracy is deeply dehumanizing. Today, only 13 percent of employees around the world are fully engaged in their work. The rest show up physically but leave much of their enthusiasm and ingenuity at home--hardly surprising given the tendency of bureaucrats to regard human beings as mere "resources." By the authors' reckoning, bureaucracy costs the global economy more than $9 trillion in lost economic output each year. Worse, despite all the hype around flat organizations and agile processes, bureaucracy is growing, not shrinking. In their provocative and practical new book, world-renowned business thinker Gary Hamel and expert coauthor Michele Zanini lay out a detailed blueprint for creating organizations that are fully human and free from the shackles of bureaucracy. Few leaders would admit to being champions of bureaucracy, but rarer still is the leader who has a plan for defeating it. Essential elements include: Calculating the hidden costs of "bureausclerosis" Ridding ourselves of toxic bureaucratic beliefs Drawing lessons from organizations that have excised bureaucracy Uprooting bureaucratic structures and processes while avoiding operational chaos Overcoming the resistance of those inclined to defend bureaucracy Learning to lead in an environment in which position and rank are no longer the keys to the kingdom The ultimate goal: organizations that are infused with the spirit of entrepreneurship, where everyone thinks like an owner, and game-changing innovation is the rule rather than the ex